2022
DOI: 10.3390/chemosensors10100388
|View full text |Cite
|
Sign up to set email alerts
|

Au-Decorated Polyaniline-ZnO Electrospun Composite Nanofiber Gas Sensors with Enhanced Response to NO2 Gas

Abstract: Ternary systems are less studied for sensing applications due to complex synthesis procedures. However, they have more sources of resistance modulation, leading to an enhanced gas response. In this study, a ternary system, namely Au-decorated ZnO-polyaniline (PANI) composite nanofibers with different amounts of PANI (10, 25, and 50 wt.%) were synthesized for NO2 gas sensing studies. First, ZnO nanofibers were synthesized by electrospinning, and then an Au layer (9 nm) was coated on the ZnO nanofibers. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 88 publications
1
4
0
Order By: Relevance
“…These results align with those reported by Ramesan et al [70], who observed a weight loss of 74.2% at 700 • C for Ag-doped ZnO-C material. The TGA curve of Au-decorated ZnO-PANI prepared by Bonyani et al [72] showed a 25% weight loss from 0 to 700 • C, which is comparable to the findings in this study.…”
Section: Tga Analysissupporting
confidence: 91%
“…These results align with those reported by Ramesan et al [70], who observed a weight loss of 74.2% at 700 • C for Ag-doped ZnO-C material. The TGA curve of Au-decorated ZnO-PANI prepared by Bonyani et al [72] showed a 25% weight loss from 0 to 700 • C, which is comparable to the findings in this study.…”
Section: Tga Analysissupporting
confidence: 91%
“…As a gas sensing material, PANI/ZnO nanohybrids have also been conrmed to exhibit the advantages of lower detection limits, faster response times, and more stable sensing signals. [139][140][141][142] As shown in Fig. 10j-l, Wang et al 143 loaded PANI/ ZnO nanohybrids on a self-formed natural grapefruit peel aerogel (GPA) to weaken the agglomeration tendency.…”
Section: Pani-metal Oxide Compositesmentioning
confidence: 99%
“…In addition, for the sample with 50 wt% PANI, many ZnO nanofibers are bonded together, which ultimately decreases the overall surface area of the ZnO nanofibers. 95 Au-decorated ZnO-NI (25 wt%) composite nanofiber gas sensor showed a response ( R g / R a ) of 50 towards 50 ppm NO 2 at 300 °C. The enhanced sensing response stemmed from the optimal amount of Au, generation of Au–ZnO Schottky junctions, and catalytic effect of Au NPs.…”
Section: Reporting Of Sensing Capabilities: Strategies and Outcomes I...mentioning
confidence: 99%